The lion and the mouse - Scott; Gavin (Thaxted Miles Kelly, 2016)
The Lion and the Mouse has been beautifully captured by Gavin Scott's enchanting illustrations. Every page showcases delightful full-bled artwork, packed with charm and detail that will enthrall children aged 3+. The story has been simply retold to appeal to young readers and listeners alike. Ages 0+